Asset Management in the Implementation of Public Sector Regional Property Disposal Systems - Rahmawati, Amalia; Fattah, Tino Kemal (Journal of Business Transformation and Strategy, 2024)
Abstract: This research aims to understand the procedures and challenges involved in the disposal of regional property at the Financial and Revenue Management Agency of Hulu Sungai Selatan Regency, following the Standard Operating Procedures (SOP). Effective management of regional property is essential as it supports the primary revenue of a region. The study employs a qualitative research method with a descriptive approach, focusing on illustrating the research object, organizational structure, main tasks and functions, and the detailed system of regional property disposal. The research findings reveal that the SOP for regional property disposal issued by the Hulu Sungai Selatan Regency Government has been well-implemented and aligns with the prescribed standards. The SOP serves as an effective guideline for property disposal, although challenges persist during the disposal process, including issues related to the property itself and the accompanying documentation. Despite these challenges, the disposal procedures at the Financial and Revenue Management Agency have adhered to the established SOP. The main obstacles encountered include insufficient documentation and properties not meeting the disposal criteria. In conclusion, the study highlights the critical role of strategic asset management in the public sector, particularly in the disposal of regional property. The recommendations provided aim to address the existing challenges and improve the efficiency and effectiveness of the property disposal process, ensuring better resource utilization and enhanced financial performance. This research contributes valuable insights for policymakers and public administrators seeking to optimize asset management practices. Keywords: Implementation of Regional Property Disposal System, Regional Asset Disposal System, Standard Operating Procedures